WT1 GENE EXPRESSION IN THE PERIPHERAL BLOOD OF PATIENTS SUFFERING FROM HEMATOLOGICAL MALIGNANCIES - Horvath Adrienne; Pap Zsuzsanna; Pavai Zoltan (European Scientific Journal, ESJ, 2014)
The WT1 gene, localized on the 11p13 region of the human genome has an important role in the development of the urogenital system, but also in the regulation of cell proliferation and differentiation. WT1 gene is overexpressed in 70-90% of leukemic cells, irrespective of the type of leukemia. WT1 gene expression in peripheral blood may detect minimal residual disease in all types of leukemias. We measured the WT1 gene expression level with qRT-PCR in the peripheral blood of 34 patients with malignancies, mainly leukemias (2 AML, 2 CML, 2 NHL, 1 HD and 27 ALL) under cytostatic treatment, 13 oncological patients who completed their chemotherapy and were in remission and 21 patients suffering from non-malignant diseases. We found WT1 gene expressions in 19 PB samples out of 47 oncological patients: 17 WT1 expressions appeared in ALL patients (15 cases under treatment and 2 post treatment) and 1-1 in a CML and NHL patient. We found a significant inverse relationship between WT1 gene positivity and time elapsed between diagnosis and blood sample examination. We did not find any relationship between WT1 gene expression and age, gender, WBC at diagnosis, FAB type of lymphoblasts, immunophenotype, risk groups, survival rate and relapse. Repeated measurements of WT1 gene expression may become a useful tool in MRD monitoring, especially in leukemias which lack specific DNA markers.